9 Early hospital discharge at 48 h following primary PCI for myocardial infarction is both safe and feasible. (9th June 2011) - Guttmann, O; Jones, D A; Rathod, K S; Akhtar, M; Ludman, A; Jain, A K; Knight, C; Mathur, A; Mohiddin, S; Wragg, A; Smith, E J
Abstract : Introduction: Reperfusion therapy with primary PCI (PPCI) has reduced rates of recurrent ischaemia and arrhythmia following ST elevation myocardial infarction (STEMI), resulting in shorter hospital stays. Discharge at 72 h in selected patients has been suggested. We investigated the feasibility and safety of very early discharge (<48 h) coupled with regular outpatient support for low-risk patients following PPCI. Methods: 2317 patients underwent PPCI for STEMI between October 2003 and May 2010 at a regional Heart Attack Centre (HAC). Demographic and procedural data were documented at the time of intervention. Patients with TIMI 3 flow, ST segment resolution, good or moderate left ventricular function, and no dysrhythmia were stratified to 48 h discharge. Remaining patients were discharged according to physician preference. All patients were reviewed at 1, 8 and 52 weeks with a multidisciplinary team including rehabilitation, heart failure, and psychology. The primary endpoint was major adverse cardiac events (MACE) included death, myocardial infarction (MI), stroke and target vessel revascularisation (TVR). All-cause mortality data were provided by the Office of National Statistics via the BCIS CCAD national audit. Outcomes were compared between those discharged at ≤48 h, 72 h, and >72 h, out to 5 years of follow-up. Results: 1079 patients (46.5%) were stratified to 48-h discharge, 14% discharged at 72 h and the remainder discharged at a median of 6 days (4.3–10), including those with complications. Patients discharged at ≤48 h were significantly younger and had a lower incidence of multi-vessel disease than those discharged at 72 h (Abstract 9 table 1 ). Remaining baseline characteristics were similar. MACE at 3 years was similar between 48-h discharge patients and 72- h discharge (9.1% vs 8.7%, p=0.7). This persisted out to 5 years (9.6% vs 9%, p=0.55). As expected patients with length of stays >72 h had significantly worse outcomes (Abstract 9 figure 1 ). Conclusion: Early discharge at 48 h is feasible and appears to be safe for patients undergoing contemporary Primary PCI.